Sed'moi sputnik . The Seventh Companion - Aronov, Grigorii; German, Aleksei (Lenfilm, 1967)
Drama. In the first revolutionary years, a professor of Law becomes entangled in the revolutionary changes and reconsiders his views. From a non-participant observer he gradually turns into a supporter of the Bolsheviks. Having made his commitment, he refuses to step back even when his life is threatened.